Management sewakadharma nurses in wangaya regional public hospitals - Susanti, Ni Luh Putu Dina; Yuliana, Euis Dewi; Suwardani, Ni Putu (International research journal of management, IT and social sciences, 2021)
The research was intended to know the management of sewakadharma nurses important to be carried out. To explore the process of implementing the management of sewakadharma and to discuss the implications of the implementation of nurse management sewakadharma on nursing and patient satisfaction at RSUD Wangaya Hospital, Denpasar City. The results show to provide sincere service following srada bhakti nurses to patients selflessly as a form of getting closer to God. To achieve patient safety and health, serving patients according to their obligations as a nurse will get the reward (pahala) according to good deeds which are conducted. It can lighten the burden on the patient and can even speed up the patient's recovery. Taking into account the biological, psychological, social and spiritual care of nursing services. Serving patients with sincerity, enthusiasm, and love. This accelerates the patient's healing process. The sincere empathy with professional services so that the patient's recovery rate increases.